About Competent Approach in Teaching Mathematics in the Social Humanitarian Classes - Alla Prus (Pedagogical Discourse, 2013)
The article deals with the plot and volume of such notions as awareness, competence, mathematical competence, competence approach; certain peculiarities of perception of mathematics by classical scholars are analyzed; peculiarities of realization of the competent approach in teaching mathematics of the pupils in the social humanitarian classes have been cleared up; the ways of its functioning have been defined.